Knowledge, attitudes, and practices toward cardiovascular complications among end-stage renal disease patients undergoing maintenance hemodialysis - Zhuo Li; Li Song; Ruifang Hua; Fangxiao Xia; Duanfeng Hu; Zhenghui Luo; Jianteng Xie; Sijia Li; Zhonglin Feng; Shuangxin Liu; Jianchao Ma; Ting Lin; et al. (BMC, 2024)
Abstract Background This study aimed to investigate the knowledge, attitudes, and practices (KAP) toward cardiovascular complications among end-stage renal disease patients undergoing maintenance hemodialysis. Methods This web-based cross-sectional study was conducted at Guangdong Provincial People's Hospital between December 2022, and May 2023. Results A total of 545 valid questionnaires were collected, with an average age of 57.72 ± 13.47 years. The mean knowledge, attitudes and practices scores were 8.17 ± 2.9 (possible range: 0-24), 37.63 ± 3.80 (possible range: 10-50), 33.07 ± 6.10 (possible range: 10-50) respectively. Multivariate logistic regression analysis showed that patients from non-urban area had lower knowledge compared to those from urban area (odds ratio (OR) = 0.411, 95% CI: 0.262-0.644, P < 0.001). Furthermore, higher levels of education were associated with better knowledge, as indicated by OR for college and above (OR = 4.858, 95% CI: 2.483-9.504), high school/vocational school (OR = 3.457, 95% CI: 1.930-6.192), junior high school (OR = 3.300, 95% CI: 1.945-5.598), with primary school and below as reference group (all P < 0.001). Besides, better knowledge (OR = 1.220, 95% CI: 1.132-1.316, P < 0.001) and higher educational levels were independently associated with positive attitudes. Specifically, individuals with a college degree and above (OR = 2.986, 95% CI: 1.411-6.321, P = 0.004) and those with high school/vocational school education (OR = 2.418, 95% CI: 1.314-4.451, P = 0.005) have more positive attitude, with primary school and below as reference group. Next, better attitude (OR = 1.174, 95% CI: 1.107-1.246, P < 0.001) and higher education were independently associated with proactive practices. Those with college and above (OR = 2.870, 95% CI: 1.359-6.059, P = 0.006), and those with high school/vocational school education (OR = 1.886, 95% CI: 1.032-3.447, P = 0.039) had more proactive practices, with primary school and below as reference group. Conclusions End-stage renal disease patients undergoing maintenance hemodialysis demonstrated insufficient knowledge, positive attitudes, and moderate practices regarding cardiovascular complications. Targeted interventions should prioritize improving knowledge and attitudes, particularly among patients with lower educational levels and income, to enhance the management of cardiovascular complications in end-stage renal disease.